2021
DOI: 10.1002/ecs2.3567
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of density dependence in juvenile salmonids: prey depletion, interference competition, or energy expenditure?

Abstract: Density dependence is a strong regulator of animal populations, operating primarily through intraspecific competition for a limiting resource. Because food is generally limited in natural environments, it is typically assumed that increasing animal density leads to reduced individual fitness through food depletion or monopolization. However, recent work demonstrates that density dependence can occur without apparent food depletion, or with virtually unlimited resources, suggesting that other mechanisms must al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…One possible explanation is that the maximum abundance in the experimental sections is a function of food availability, as is typical of many populations following BH models (Wootton, 2012). This is plausible because bioenergetic models have shown that food is a limiting factor of somatic growth and survival at higher densities in these populations (Matte et al, 2021). In addition, overcompensation in the Ricker model is often driven by predation, reproductive interference, and/or cannibalism by adults (Wootton, 2012), but the present system does not have any notable predators (Hutchings, 1990), and adults were excluded from experimental sections.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…One possible explanation is that the maximum abundance in the experimental sections is a function of food availability, as is typical of many populations following BH models (Wootton, 2012). This is plausible because bioenergetic models have shown that food is a limiting factor of somatic growth and survival at higher densities in these populations (Matte et al, 2021). In addition, overcompensation in the Ricker model is often driven by predation, reproductive interference, and/or cannibalism by adults (Wootton, 2012), but the present system does not have any notable predators (Hutchings, 1990), and adults were excluded from experimental sections.…”
Section: Discussionmentioning
confidence: 97%
“…Recruitment models with biomass were improved by incorporating the effects of temperature, but not models with density. This is not surprising, given that temperature is an important driver of the underlying patterns of density dependence in this system (Matte et al, 2020a;Matte et al, 2021). More specifically, increasing temperatures result in stronger density-dependent mortality per unit of growth in these populations, but at different rates among populations (Matte et al, 2020a).…”
Section: Recruitment Models Are Improved By Incorporating the Effects...mentioning
confidence: 87%
See 3 more Smart Citations